Congenital Midline Defect in Pituitary Dwarfs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
MRI evaluations of pituitary volume, and clinical and endocrine findings in 101 pituitary dwarfs with congenital idiopathic growth hormone deficiency (CIGHD) are reported from the Departments of Neuroradiology and Pediatrics, Scientific Institute H San Raffaele, Milan, Italy.